Methodological Aspects of Forecasting Skilled Labor in Context of Innovation Transformations (of the Russian Economy) - GRETCHENKO, A. I.; NIKITSKAYA, E. F.; GRETCHENKO, A. A.; DEMENKO, O. G. (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
Innovation forecasting objectively determines the ways of a state’s development based on the global technological mainstream, long-term national goals, capacities and limitations for reaching them, planning of concrete actions for the future. A key role in creation of strategic trends of formation of an innovation economy is played by the human capital development, based on systematic analysis of the practice of forecasting the economy’s demand for skilled labor from a professional qualification viewpoint. The article presents an analytical overview of methodology, modern international experience and Russian practice of forecasting the economy’s demands for skilled labor from the standpoint of labor market development in conditions of development of innovation processes. This study was financed by a grant from the Plekhanov Russian University of Economics.